"الآراء الأصوليَةُّ لأبي الفضلِ الخوَارزميِّ الحنفيِّ صاحب "ا لكبريت الأحمر - حليم، مدبر; Halim, Müdebbeur; أتاش، أويس; Ateş, Üveys (Fatih Sultan Mehmet Vakıf Üniversitesi, 2025)
يُعدُّ الزركشيُّ من أئمَّةِ علمِ أصولِ الفقه، الذين اعتَنَوا بنقلِ آراءِ الأصوليِّين؛ بل نقلَ الكبريتُ « عن مُصنَّفاتٍ نادرة، وهي في حُكمِ المَفقُودِ في زمننا، ومن تلكَ المصنَّفاتِ لأبي الفضلِ الخَوارزميِّ. » الأحمرُ ارتأتْ هذه الدراسةُ البحثَ في آراءِ أبي الفضلِ الخوارزميِّ، لكن تظهرُ صعوبةُ البحثِ في عدمِ وُقوعِ هذا الكتابِ بين أيدينا، ولا معرفة بحالِ مؤلِّفه، ولذا كان اعتمادُ البحثِ على ما نقلهُ الزركشيُّ. طبيعةُ البحثِ تُحتِّمُ على الباحثِ أن يكونَ على وَفْقِ المَنهجِ الاستقرائيِّ؛ بجمعِ كلِّ ثمَّ المنهجِ التحليليِّ؛ بتحليلِ تلك ،» الكبريتِ الأحمر « الآراءِ الأصوليَّةِ التي نُسِبتْ لصاحبِ الآراءِ الأصوليَّة، ومُقارنَتِها بآراءِ الأصوليِّين، والمنهجِ الاستنباطيِّ؛ باستنباطِ ما اختارَهُ أبو الفضلِ الخوارزميُّ، مع ذِكْرِ أهمِّ النتائجِ، والتوصِيَات.

Al-Zarkashi is considered one of the prominent scholars in the field of Usul al-Fiqh (principles of Islamic jurisprudence). He devoted great attention to transmitting the views of earlier scholars, often citing rare works that are now considered lost. Among these is Al-Kibrit Al-Ahmar by Abu al-Fadl al-Khwarizmi. This study aims to examine the jurisprudential opinions of Abu al-Fadl al-Khwarizmi. However, a major challenge lies in the fact that Al-Kibrit Al-Ahmar is not extant, and little is known about its author. Therefore, the research relies entirely on the citations and references provided by Al-Zarkashi. The nature of this research necessitates an inductive approach—gathering all jurisprudential opinions attributed to the author of Al-Kibrit Al-Ahmar. Additionally, an analytical approach is employed to examine these opinions and compare them with those of other jurists. Finally, a deductive approach is used to infer the specific stances of Abu al-Fadl al-Khwarizmi, concluding with key findings and recommendations.
The Fundamental Jurisprudential Opinions of Abu al-Fadl al-Khwarizmi, the Hanafi Scholar and Author of “Al-Kibrit Al-Ahmar
Keywords: أصولُ الفقه; الحنفيَّة; أبو الفضلِ الخوارزميُّ; البحرُ المحيط; الكبريتُ الأحمر; Usul al-Fiqh; Hanafi Jurisprudence; Abu al-Fadl al-Khwarizmi; Al-Bahr Al-Muhit; Al-Kibrit Al-Ahmar